Desenvolvimento humano à luz das teorias de Amartya Sen e as contribuições do IFTO na promoção das liberdades instrumentais de seus colaboradores em Colinas - TO. - Pinto, Lucas Lopes (Universidade Federal do Tocantins, 2023)
This dissertation seeks to identify the development from the conception of instrumental freedoms of the economist Amartya Sen (2000). This research was developed in the process of identifying the role of the Federal Institute of Tocantins (IFTO) and its possibilities to promote human development, through instrumental freedoms, to collaborators: teachers and technical-administrative education professionals who work on the Campus de Colinas do Tocantins. The theoretical references of this research were structured considering theoretical concepts about the development of Sen (2000), with emphasis on instrumental freedoms: Political Freedoms, Economic Facilities, Social Opportunities, Guarantees of Transparency and Protective Security. We used, in this work, the monographic and descriptive method, together with the quali-quantitative analysis of the collected data. The documentary research took place to collect data and general information from the Federal Institute. With regard to field research, questionnaires were applied to employees who declared their socioeconomic characteristics and their possible instrumental freedoms. This time, after analyzing the forms and based on the bibliography studied, which at the Instituto Federal de Colinas do Tocantins, its collaborators presented aspects of development in relation to the five instruments addressed. We found that the Federal Institute (IF) enables its employees, human development through instrumental freedoms, identified in democratic actions, quality of life, institutional support and individual and social well-being. Practices that directly reflect on the improvement of the quality of public servants who work in the municipality of Colinas do Tocantins.